A bibliometric analysis of collaboration skills in education (2019-2021) - Sri Marmoah; Rivan Gestiardi; Sarwanto Sarwanto; Chumdari Chumdari; Ika Maryani (Intelektual Pustaka Media Utama, 2022)
One indicator of 21st century skills is collaboration; essential skill students must acquire in century learning. This study aimed to reveal research trends over the last three years based on the start of COVID-19 by using content analysis and reviewing bibliometric results related to articles with collaboration keywords. For bibliometric mapping analysis, a total of 500 articles were accessed, and for content analysis, 31 articles were selected between 2019-2021 based on Google Scholar's database corresponding to the education field study of the research. The results showed that digital